Imiquimod 5% as Adjuvant Therapy for Incompletely Excised Infiltrative Nodular Basal Cell Carcinoma and Dermoscopy to Monitor Treatment Response. Issue 4 (December 2015) - Roldán-Marín, Rodrigo; Toussaint-Caire, Sonia
Abstract Introduction A relatively novel application for dermoscopy is its use in the monitoring of topical treatment response for non-melanoma skin cancer. Basal cell carcinoma (BCC) is the most frequent type of skin cancer in humans. Surgical excision is still considered the "gold-standard" of treatment. However, a number of topical therapies are now available for the treatment of different types of basal cell carcinoma. Case Report This case report exemplifies the usefulness of dermoscopy in the monitoring of residual disease after incomplete surgical excision and also in the monitoring of topical treatment response. Imiquimod 5% cream acts as a topical immune response modifier promoting a Th-1 immune response enhancing the removal of neoplastic cells and has proven to reduce deregulated Hedgehog (HH)/GLI signal strength independent of Toll-like receptor signaling, which makes it a valuable adjuvant topical therapy for the treatment of basal cell carcinoma. Conclusion Imiquimod 5% cream is a valuable adjuvant therapy for the treatment of incompletely excised BCC. This case report adds further evidence to the usefulness of dermoscopy in the assessment and monitoring of treatment outcome.